2015
DOI: 10.1111/jgs.13489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Multimodal Exercise Program on Physical Function, Falls, and Injuries in Older Women: A 2‐Year Community‐Based, Randomized Controlled Trial

Abstract: Twenty-four months of multimodal exercise enhanced physical functioning in women aged 70 to 80 with a history of falls. Although the total number of falls was not lower than in controls, the rate of medically attended injurious falls was more than 50% lower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(87 citation statements)
references
References 39 publications
3
76
0
8
Order By: Relevance
“…At the end of the intervention, there were no statistically significant changes in ADL, IADL or mobility scores in any group, nor between-group differences. Also, the groups did not differ in the amount of physical activity outside the intervention [21]. …”
Section: Resultsmentioning
confidence: 99%
“…At the end of the intervention, there were no statistically significant changes in ADL, IADL or mobility scores in any group, nor between-group differences. Also, the groups did not differ in the amount of physical activity outside the intervention [21]. …”
Section: Resultsmentioning
confidence: 99%
“…A previously published article showed that the prevalence of sarcopenia in this study population was low (0.9–2.7%) at baseline . During the intervention, mean total body lean mass and fat mass changed only slightly in both groups . In Finland, mean protein intake of healthy community‐dwelling older women has been found to be sufficient according to recommended levels, so protein intake was not assessed.…”
mentioning
confidence: 79%
“…Programas de exercícios físicos para idosos têm apresentado melhoras no incremento e manutenção da força muscular (38) Os relatos de quedas nos últimos seis meses foram maiores (p<0,001) entre os idosos não inseridos nos programas de exercícios (Tabela 3). As quedas e suas consequentes lesões são consideradas um dos problemas médicos mais comuns e graves experimentados pelos idosos (48). E neste sentido, os programas de exercícios para população idosa têm se mostrado eficiente na prevenção de quedas, uma vez que melhora o tempo de reação e os reflexos protetores (48), bem como a força muscular (41) (40).…”
Section: Discussionunclassified